Prevalence of Diabetes in Patients with Primary Open Angle Glaucoma (International Journal of Food and Nutritional Sciences, 2022)
Background:Diabetes mellitus represents a growing international public health issue with a near quadrupling in its worldwide prevalence since 1980. Though it has many known microvascular complications, of which vision loss from diabetic retinopathy is one of the most devastating for affected individuals.Objective:One of the risk factors for primary open angle glaucoma is diabetes mellitus (DM). This study was conducted to determine the prevalence of T2DM and investigate the connection between the diabetes and intraocular pressure (IOP) in POAG patients.Methodology:Patients aged >40 years already diagnosed with glaucoma and using prescription medications or anti-glaucoma therapy, were included in the study. Using Goldmann tonometry, the intraocular pressure was measured. The data was analyzed.Result:Out of 114 POAG patients, 61 men and 53 women participated in the study. Diabetes affected 27.9% of the 61 males, but only 24.5% of the 53 females. However, the study showed a negligible correlation betweendiabetes and IOP.Conclusion: Any of the other clinical and diagnostic measures of POAG did not correlate with diabetes mellitus.